Use of intrauterine balloon tamponade in successful conservative management of life threatening menorrhagia in a patient with idiopathic thrombocytopenic purpura and severe anemia - Agrawal, Rekha; Shintre, Hemant; Rani, Bindu; Agrawal, Krishna; Agrawal, Aniruddh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 45-year-old woman was brought into the emergency ward of a tertiary care hospital. The patient gave a history of excess bleeding and passage of clots per vaginum since the past 15 days. The patient had a history of severe headaches, body ache, giddiness and vomiting. She was diagnosed with idiopathic thrombocytopenic purpura (ITP) and severe anemia six months before this incidence. The authors performed a diagnostic pelvic and transvaginal ultrasound and reported the presence of uterine fibroids. They determined that these fibroids had aggravated the bleeding which was caused by ITP. The diagnosis of ITP coupled with severe anemia prevented the authors from using the traditional approach of a hysterectomy in such a case. She was administered tranexamic acid, testosterone enanthate, blood, intravenous immunoglobulins, steroids and platelets transfusion. Uterine artery embolization (UAE) was tried for arresting menorrhagia, but was unsuccessful. Finally, a Bakri® balloon, normally used for management of post-partum hemorrhage (PPH), was inserted and retained for 48 hrs.. The bleeding gradually ceased and significant improvements in hematocrit and platelet count were observed. However, the patient then suffered from a deep vein thrombosis (DVT) in the lower extremity, which was treated with low molecular weight heparin (LMWH), a thrombectomy and an Inferior vena cava Filter. Patient was advised a hysterectomy to curb her symptoms, however, she was too exhausted of surgical procedures and refused. Therefore, the authors decided to employ the use of Selective Estrogen Receptor Molecule Therapy (SERM). 3-months post-intervention, patient is thriving and stable.